Detecting malnutrition risk and obesity after spinal cord injury: a quality improvement project and systematic review. Issue 11 (November 2018) - Wong, Samford; Kenssous, Noureddine; Hillier, Clare; Pollmer, Sharon; Jackson, Penny; Lewis, Sarah; Saif, Mofid
Abstract Background/objectives Malnutrition and overweight are a major concern after spinal cord injury (SCI). There is limited information available for prevalence of malnutrition, overweight and nutrition screening compliance. The aim of this study is to (1) determine whether the quality improvement initiative is successful in improving nutrition screening and to (2) systematic review the literature on prevalence of malnutrition and overweight after SCI. Subjects/methods The quality improvement project was conducted during November 2013 to October 2017. Nutrition screening data (presence of a correctly completed Spinal Nutrition Screening Tool (SNST) within 24 h of admission) were collected weekly. Literatures on disease-related malnutrition prevalence in adult SCI patients published from inception to 17 March 2017 were included in the systematic review. Results Two thousand four hundred and sixty-two SCI (49.3% tetraplegia; 47.6% complete SCI) patients (mean age: 76.7 ± 16.2 years, 70.6% men) were included. Nutrition screening compliance increased significantly overtime (2013–2014: 49.3%; 2014–2015: 69.7%; 2015–2016: 80.7%; 2016–207: 76.7%, p < 0.01). Eighty-four articles were identified from the systematic review, of these nine studies with 9265 SCI patients were included. There was considerable variability in methodology and prevalence of malnutrition risk (three nutrition screening tools were reported: body mass index (BMI); Malnutrition Universal Screening Tool; SNST). The prevalence of undernutrition was in the range of 40–50%. Three different BMI cutoffs were reported as overweight's cut-off (>22, >23 and >25 kg/m2 ). The prevalence of overweight was in the range of 45–69.2%. Conclusions Malnutrition and overweight is a highly prevalent condition after SCI. Further research is warranted to characterise screening practices and identify evidence-based interventions to this ongoing and costly clinical and public health issue.